Evaluation of the Implementation of Blockchain Technology in Financial Transactions in the Public Sector: Systematic Literature Review - Arviona Zahra Sophia; Lulus Kurniasih (LP2M IAIN Palopo, 2026)
Blockchain technology is increasingly seen as a disruptive instrument in strengthening transparency and accountability in public financial management, especially in the midst of increasing demands for clean and responsive governance, but its implementation still faces conceptual and empirical gaps related to effectiveness and institutional readiness. This study aims to systematically evaluate the application of blockchain in the context of public finance by identifying key benefits, structural challenges, and best practices that are developing in the global literature. The method used is a Systematic Literature Review (SLR) based on the PRISMA protocol with the main data source from the Scopus database, resulting in 30 selected articles that were analyzed through a bibliometric approach and qualitative content analysis to map research trends and dominant themes. The results show that blockchain significantly increases transparency through a distributed and immutable system of record, as well as strengthens accountability through automated verification mechanisms, although its implementation is constrained by regulatory complexity, digital infrastructure limitations, and organizational resistance. In addition, the literature review is still dominated by the issue of transparency and technological innovation, while the audit and corruption prevention dimensions are relatively underexplored. This study concludes that blockchain has strategic potential in transforming public financial governance, but its success is highly dependent on the readiness of the regulatory ecosystem, technological capacity, and stakeholder acceptance. The implications of this study include strengthening integration between governance theory and technology adoption, as well as providing a strategic framework for policymakers in optimizing blockchain implementation